Titanium Dioxide Formation Via Anodization And Thermal Oxidation For Photoreduction Of Chromium (Vi) - Sazalli, Nurliyana Abu Hasan (2019)
This study investigated on the photocatalytic performance to reduce Cr(VI) to Cr(III) in aqueous solution of TiO2 nanotubes (NTs) and nanowires (NWs) synthesised by oxidation of titanium, anodically and thermally, respectively. TiO2 NTs were produced in fluoride containing electrolyte whereas TiO2 NWs were produced in potassium containing oxidation environment. During these fabrication processes, TiO2 was found to contain ions which were required for the growth of the nanostructures. In NWs, potassium ions were found to be the main impurity whereas in NTs, fluoride ions were detected to be incorporated within the oxide. EDX in SEM was used to study the amount of impurities in the oxide. It was found that anodic TNTs were consisted of 1.89 wt % of fluorine. Thermally oxidised NWs contained 7.54 wt% of potassium contamination. Therefore, as to compare if the impurities affect the Cr(VI) reduction process, TiO2 films were also created either by anodic or thermal oxidation in the absence of fluoride ions and potassium ions, respectively. The resulting films were compact without any noticeable nanostructures and from EDX the films were free from contamination. The crystal phases of the anodic or thermal oxidised TiO2 were also studied. It was found that anodic NTs were comprised of anatase as shown from XRD and Raman spectroscopy whereas compact TiO2 was consisted of a mixture of amorphous and rutile. Thermally oxidised TiO2 compact and NWs on the other hand were consisted of both rutile oxide. NTs, NWs and compact TiO2 were tested in a photocatalysis experiment to reduce Cr(VI) to Cr(III). It was found that compact anodised TiO2 can reduce down to 48.36% after 20 minutes. Whereas annealed NTs can reduce 5.86% after 20 min. This indicated that the NTs have less ability to reduce Cr(VI) compared to compact anodic film. Similarly, thermally oxidised titanium with compact structure can reduce 28.04% compared to 14.48% NWs after 20 min. However, it was found that after 50 min , all four samples has reach almost 100% of reduction.